Ethics in the real world 82 brief essays on things that matter - Singer, Peter 1946- (Princeton University Press, 2016)
In Ethics in the Real World, Singer shows that he is also a master at dissecting important current events in a few hundred words. In this book of brief essays, he applies his controversial ways of thinking to issues like climate change, extreme poverty, animals, abortion, euthanasia, human genetic selection, sports doping, the sale of kidneys, the ethics of high-priced art, and ways of increasing happiness. Singer asks whether chimpanzees are people, smoking should be outlawed, or consensual sex between adult siblings should be decriminalized, and he reiterates his case against the idea that all human life is sacred, applying his arguments to some recent cases in the news.